Proton and anion transport across the tonoplast vesicles in bromeliad species - Pereira, PN; Smith, JAC; Purgatto, E; Mercier, H (CSIRO Publishing, 2017)
Crassulacean acid metabolism (CAM) is one of the key innovations in the Neotropical family Bromeliaceae that has enabled many of its species to occupy seasonally water-limited terrestrial environments or microclimatically arid epiphytic niches. However, the relationship between CAM activity and the transport processes responsible for vacuolar organic-acid accumulation at night has not been systematically explored in this family. In the present investigation, ATP- and PPi-dependent proton transport rates were studied in tonoplast membrane vesicles isolated from leaves of six CAM and one C3 species of bromeliads. A consistent feature of these species was the high activity of the tonoplast ATP-driven H+ pump, which, when averaged across the seven species tested, showed a higher specific activity than the tonoplast PPi-driven H+ pump. For all CAM species, the rate of ATP-dependent proton transport into the tonoplast vesicles was strongly influenced by the nature of the balancing organic-acid anion, which displayed the following order of effectiveness: fumarate > malate > citrate. Measurements of leaf organic-acid content in six CAM bromeliads at dusk and dawn showed that nocturnal accumulation of malate exceeded citrate by a factor of ~2.4–20.0-fold in five of six bromeliad species used in this study, demonstrating a close correlation between the CAM rhythm and the intrinsic properties of the vacuolar membrane across which these organic acids are transported.